Young people’s perceptions of housing access in a small and remote island: The case of Madeira - Ornelas, J. C. B.; Freitas, C. M. F. de.; Rosa, Á. A. da. (Small States and Territories, 2024)
Young people encounter numerous barriers to housing access, driven by the prolonged duration of educational pursuits, associated with the high costs of education, job insecurity, the rapid escalation of housing prices, and the stringent requirements for obtaining mortgage loans. This challenging scenario is further exacerbated by the lack of viable housing alternatives, leading to widespread dissatisfaction among youth who feel overlooked in public housing programmes. In the context of small islands, these issues are often intensified due to limited resources. This study aims to explore the perceptions of young people from the subnational island jurisdiction of Madeira about the primary obstacles to housing access and the most helpful policy interventions in this regard. The findings indicate that the predominant issue in Madeira is the high cost of housing in the private market, and the most valued social policy involves rental support. This research underscores the critical role that government policies play in addressing housing accessibility, particularly on islands.